Mesoporous PdBi film as efficient electrocatalyst for ethanol oxidation reaction. (14th April 2021) - Ren, Siyu; Du, Dawei; Ma, Lian; Li, Cuiling
Abstract: Developing electrocatalysts that can completely oxidize ethanol oxidation is critical for commercializing direct ethanol fuel cells. Here, we tailored synthesis of mesoporous PdBi films by employing an electrochemical-assisted micelle assembly approach. The as-prepared film exhibited superior electrocatalytic activity and stability toward ethanol oxidation reaction, which is promising forpractical applications.